Anthropology of female identity in the philosophy of Edith Stein - Boluarte Drago, Analyda (2020)
In this paper, Edith Stein's conception of women is analyzed from the perspective of philosophical anthropology, with a predominantly phenomenological approach. Her ideas are presented as a foundation for contemporary philosophical reflection on women, seen as a person who possesses unquestionable dignity. Likewise, the topicality of her approaches is highlighted, mainly what Edith Stein called the “feminine specific”.